1998
DOI: 10.1080/13557858.1998.9961860
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ethnoracial group and functional level in older persons

Abstract: The objective of this study was to determine: (1) the differences between blacks, Latinos, and whites in relation to functional level, (2) whether these differences could be entirely explained by differences in socioeconomic status (SES) for both blacks and Latinos, and (3) which SES indicators might account for differences in function. Data from the 1570 respondents in the Growing Older in New York City Study, a representative sample of black, Latino, and non-Latino white persons, age 65 years and over, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…76 Preventing or postponing functional disability among older people must be a major goal for public health. Chiropractors, by focusing on structural health problems, nutrition, exercise, and drugless therapy, have a great deal to offer older persons.…”
Section: Discussionmentioning
confidence: 99%
“…76 Preventing or postponing functional disability among older people must be a major goal for public health. Chiropractors, by focusing on structural health problems, nutrition, exercise, and drugless therapy, have a great deal to offer older persons.…”
Section: Discussionmentioning
confidence: 99%
“…Mexican-Americans are the largest Latino subgroup, followed by Puerto Ricans and Cubans (Carter-Pokras and Woo 1999; Halgunseth 2004). However, Latino elders are underrepresented in discussions of both minority elders and Latino families (Berkman and Gurland 1998; Hurtado 1995). …”
Section: Latinosmentioning
confidence: 99%
“…Older men are more likely than women to be married, and Latinos of all ages are more likely to live in multigenerational households than Whites (Berkman and Gurland 1998; Cohen and Casper 2002; Sarkisian et al 2007), in part due to economic patterns (Lee and Aytac 1998). Thus, Latino elders are less likely than Whites to live alone or in institutions (Burr and Mutchler 1999), although Puerto Ricans have slightly higher rates of single living than do Mexican-Americans (Zsembik 1993) and residence varies by immigration history for Mexican-Americans (Blank 1998).…”
Section: Latinosmentioning
confidence: 99%
“…It has also been reported that community-dwelling older adults over the age of 65 years of Latino descent are more functionally impaired compared to whites and blacks [5]. The impact of the projected ethnic shift in the older adult population on the demand for health care services is poorly understood, particularly in those 80 years and older [1, 6].…”
Section: Introductionmentioning
confidence: 99%